Development of Integration Processes in Agro-Industrial Sphere - Berezina, Liudmyla; Diadyk, Tetyana; Zahrebelna, Iryna; Maksymenko, Oleh (International Journal of Engineering and Technology, 2018)
Integration processes in the agro-industrial sector are an important factor in increasing the efficiency of its functioning by obtaining a synergistic effect in various economic areas, in particular, economic, organizational, managerial, and social.As a result of solving the main tasks of the article due to its purpose, the main factors that influence the integration processes in the agro-industrial sphere are revealed; the basic criteria of their systematization are determined; the main tendencies of the integration processes of agro-industrial formations are studied and EBITDA is calculated, through which the impact of capital on efficiency is estimated; the main stages of integration processes management are singled out and the conceptual model of integration processes development of agro-industrial formations is proposed.Â Â